Optimasi Aplikasi Penjadwalan Kuliah Menggunakan Algoritma Genetik - Syahrul Mauluddin; Iskandar Ikbal; Agus Nursikuwagus (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Course Scheduling is a routine activity at a college and it is a very important activity for the implementation of condusive academic activities. Problems that often occur in course scheduling are the length of the schedule making process and the clashes due to the many rules that must be considered. This problem happened in Indonesian Computer University at accounting major because the lecture scheduling process was still done conventionally. Given the importance of this scheduling process, optimization steps are needed so that the scheduling process will be faster and the schedule clashes can be minimized. Based on the problems, this research purpose is to optimize course scheduling application using genetic algorithm. The system approach method used in the development of course scheduling applications is object-oriented approach, with system development methods namely prototype models. to build the application we use the Java SE programming language with MySQL database. The conclusion of this study is that the implementation of genetic algorithms to course scheduling applications is able to achieve 0 (zero) clash which means very optimal, and view by time the result is very fast with an average of 1.003 seconds from 10 times the schedule creation attempt.